2008
DOI: 10.1021/jm7014149
|View full text |Cite
|
Sign up to set email alerts
|

4-Benzyl-1H-imidazoles with Oxazoline Termini as Histamine H3 Receptor Agonists

Abstract: Research on the therapeutic applications of the histamine H3 receptor (H3R) has traditionally focused on antagonists/inverse agonists. In contrast, H3R agonists have received less attention despite their potential use in several disease areas. The lower availability of H3R agonists not only hampers their full therapeutic exploration, it also prevents an unequivocal understanding of the structural requirements for H3R activation. In the light of these important issues, we present our findings on 4-benzyl-1H-imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 60 publications
3
33
0
Order By: Relevance
“…The pyrimidine nitrogen chemical shifts in the (4-pyrimidyl)methylenetriazole series 5 (δ = 291 ppm, Table 5, entries [30][31][32][33] are in agreement with literature data for 4-alkylpyrimidines (δ ≈ 291 ppm). [34,40] Unfortunately, the applied resolution of the 1 H-…”
Section: Pyridine Pyrimidine and Pyrazine Ringssupporting
confidence: 89%
See 1 more Smart Citation
“…The pyrimidine nitrogen chemical shifts in the (4-pyrimidyl)methylenetriazole series 5 (δ = 291 ppm, Table 5, entries [30][31][32][33] are in agreement with literature data for 4-alkylpyrimidines (δ ≈ 291 ppm). [34,40] Unfortunately, the applied resolution of the 1 H-…”
Section: Pyridine Pyrimidine and Pyrazine Ringssupporting
confidence: 89%
“…A modified literature procedure, previously used for the reduction of the analogous benzyl alcohol derivatives, was applied. [30] The results are collected in Table 4. [a] Yield of isolated pure product.…”
Section: Resultsmentioning
confidence: 99%
“…The combined organic layer was dried (Na 2 SO 4 ), evaporated, and purified with SiO 2 column chromatography (EtOAc/hexane = 2:3, then 1:1) to give 20 as a white solid (2.75 g, quant). 1 2-(1-(tert-Butoxycarbonyl)piperidin-4-yl)-2-(1-trityl-1H-imidazol-4-yl)acetic Acid (21). A solution of 20 (2.75 g, 5.17 mmol) in 2-ethoxyethanol (5 mL) was added to the 40% KOH aqueous solution (20 mL), and the mixture was stirred at 100°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…15 Interestingly, H3 agonists of another type, possessing a less basic side chain or highly lipophilic moiety in place of the terminal basic nitrogen atom, have been discovered, as represented by immethridine 5, UCL 1470 8, and our compound 1. 10,13,[16][17][18][19][20][21] We have found that the introduction of an alkylated benzene ring to the terminal nitrogen atom of histamine, 4-(2-(N-(alkylphenyl)amino)ethyl)-1H-imidazole derivatives, partially maintained the agonistic activity of histamine. 10 Noticeably, para CF 3 and para t-Bu substituents on the benzene ring improved the H3 receptor affinity, and the alteration of its aminoethyl spacer part to the thioether of 1 increased the agonistic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Iodinated aromatic heterocycles are an important class of intermediates in organic synthesis which are extensively utilized in the medicinal chemistry and process development groups of pharmaceutical companies and in academic laboratories [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%